Perancangan Smart Surveillance System Pada Smarthome Menggunakan NI MyRIO - Novaria Elsari Ryzkiansyah; Wijaya Kurniawan; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Smarthome is an innovation in providing quality comfort in everyday activities. The presence of thieves and stranger into the house gives a fear to the home owner in doing activities inside or outside the home. From these problems, in this study, home modeling and implementation of security systems that can prevent the theft act is required. The process of monitoring the thief and stranger in the house is done using the camera and accelerometer sensor, and use the alarm and email to obtain information of the thief and stranger. As the main controller used NI MyRIO. This study uses template matching method to determine comparing and detect home conditions when the system is run with changing conditions. Testing is done with several different scenarios, from 5 times the testing of shooting templates having the difference of error time of 0.06%. the comparative image used on the system has an average error time difference of 0.33%. From the accelerometer sensor and buzzer experiments as much as 12 times the results obtained eleven successes and one failed. For an email server that can be used into the system is smtp.gmail.com with port 587.